Effectiveness of Lavender Leaf Pudding (Vigna Sinensis L) on Increasing Breast Milk Production in Breastfeeding Mothers - Sitti Chalimathul Adnin; Endah Wahyutri; Nilam Noorma (PT FORMOSA CENDEKIA GLOBAL, 2023)
Breast milk is mother's milk that comes out after giving birth. The problem that can hinder exclusive breastfeeding is the production of breast milk that has not been smooth. One of the reasons is due to the lack of knowledge of mothers about the nutritional status of breastfeeding mothers. By giving lavender leaves, it is hoped that it can increase milk production. The purpose of this study was to determine the effectiveness of lavender leaf pudding (Vigna sinensis L) on increasing milk production in breastfeeding mothers in the working area of Teluk Bayur Health Center, Berau District. The research design used was a Quasi Experiment with a non-equivalent control group research design. The sample in this study were breastfeeding mothers in the working area of the Teluk Bayur Health Center, Berau Regency, as many as 36 respondents using a purposive sampling technique